2023
DOI: 10.1302/2633-1462.46.bjo-2023-0042.r1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of primary malignant tumours, rates of pathological fracture, and mortality in the setting of metastatic bone disease

Abstract: AimsThe modern prevalence of primary tumours causing metastatic bone disease is ill-defined in the oncological literature. Therefore, the purpose of this study is to identify the prevalence of primary tumours in the setting of metastatic bone disease, as well as reported rates of pathological fracture, postoperative complications, 90-day mortality, and 360-day mortality for each primary tumour subtype.MethodsThe Premier Healthcare Database was queried to identify all patients who were diagnosed with metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…У разі раку молочної чи передміхурової залоз симптоми, пов'язані з метастазами, часто є першою ознакою захворювання [11,12]. Деякі пацієнти можуть мати патологічні переломи й ускладнення через них: наприклад, неврологічні порушення за умов метастаз у хребті (адже загальновідомо, що хребет є найпоширенішим місцем метастазування) [13,14].…”
Section: обговоренняunclassified
“…У разі раку молочної чи передміхурової залоз симптоми, пов'язані з метастазами, часто є першою ознакою захворювання [11,12]. Деякі пацієнти можуть мати патологічні переломи й ускладнення через них: наприклад, неврологічні порушення за умов метастаз у хребті (адже загальновідомо, що хребет є найпоширенішим місцем метастазування) [13,14].…”
Section: обговоренняunclassified
“…A 2020 study of the SEER database from 2010 to 2013 reported that 5% of patients have bone metastases at presentation, with the highest prevalence in breast and prostate cancer patients [ 1 ]. A 2023 study of the Premier Healthcare Database from January 2015 to December 2020 found that the primary sites among patients with bone metastases were the lungs (25%), prostate (19%), and breasts (19%) [ 2 ]. A 2015 study based on the Oncology Services Comprehensive Electronic Records database found that breast cancer patients experience a significant symptom burden from bone metastases, including pain, fatigue, sleeping problems, and neuropathic symptoms [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 study based on the Oncology Services Comprehensive Electronic Records database found that breast cancer patients experience a significant symptom burden from bone metastases, including pain, fatigue, sleeping problems, and neuropathic symptoms [ 3 ]. In the Premier Healthcare Database study, the 90-day mortality after a pathological fracture was about 10% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%